Peningkatan Kinerja Pada Perusahaan Dengan Menerapkan Corporate Governance - Zulia Maisyara Nasution (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
ABSTRACT Corporate governance is measured using the CGPI (Corporate Governance Perception Index) from the rankings compiled by the IICG (Indonesian Institute of Corporate Governance) and company performance is measured using the Return on Equity and Tobin's Q. The statistical method used is multiple linear regression analysis. The research sample is a company listed on the Jakarta Stock Exchange and participated in a survey conducted by IICG in 2005-2007 and included in the CGPI ranking. Based on the output of hypothesis testing, the conclusion can be drawn that corporate governance affects the company's market performance. This indicates that the greater the market value of the assets, the greater the willingness of investors to make more sacrifices for the company, so that the company has a very strong brand image because the implementation of GCG (Good Corporate Governance) is related to improving the company's image. Companies that practice GCG will experience improved image and increase corporate value. However, corporate governance has no direct effect on the company's operational performance. This indicates that the issuer's awareness is still low in implementing GCG. The company management has not been interested in long-term benefits related to the implementation of GCG so that they feel that they can run without GCG.